2015
DOI: 10.1007/s40520-015-0329-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory characteristics of active and healthy aging (AHA) in octogenarian men

Abstract: Less than 5 % enjoyed active and healthy aging over their life course, which was significantly related to markers of frailty but not to the traditional vascular risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Furthermore, earlier studies of the HBS cohort have shown associations between cardiovascular risk factors in midlife and health-related quality of life in old age [ 16 19 ]. However, the cross-sectional study in old age [ 7 ] suggested that cardiovascular risk factors were not significantly related to AHA, which may be due to reverse causation and the effects of medications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, earlier studies of the HBS cohort have shown associations between cardiovascular risk factors in midlife and health-related quality of life in old age [ 16 19 ]. However, the cross-sectional study in old age [ 7 ] suggested that cardiovascular risk factors were not significantly related to AHA, which may be due to reverse causation and the effects of medications.…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, 839 men of the present study responded to mailed survey, and the criteria of AHA were defined by Rantanen et al [ 7 ] as: (1) being alive, (2) responding to the mailed questionnaire survey (reflects social functioning), (3) no subjective cognitive problems (self-reported in the survey according to the memory item in the Clinical Dementia Rating; reflects cognitive functioning), (4) feeling of happiness (self-reported in the survey, RAND-36 item; reflects psychological functioning), (5) no difficulties in activities of daily living (ADL) (self-reported in the survey; reflects physical functioning), and (6) no significant chronic diseases (cardiovascular diseases, Parkinson disease, Alzheimer disease, rheumatoid arthritis, cancer, obstructive pulmonary disease, diabetes; self-reported in the survey; reflects physical health).…”
Section: Design and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we must consider healthy ageing in a life course perspective. Few studies exist, but in a recent long-term study from early midlife to old age, only 5 % of the original cohort of octogenarian men experienced ''healthy ageing'' (defined by the absence of important non-communicable diseases, intact memory and ADL, happy and socially active) [9]. In older survivors, the proportion has been higher, for example 12 % in a national US sample of 65?…”
mentioning
confidence: 99%